Vulnerable frequency as an independent prognostic factor for sudden sensorineural hearing loss - Liang, Chaoqun; Fang, Qi; Chen, Hongjun; Wang, Zhixian; Qiao, Xiangyun; Liao, Yaqi; Lv, Chenxi; Chen, Mo; Li, Lingxue; Yang, Jianming (Frontiers in Neurology, 2022)
Objectives: Sudden sensorineural hearing loss (SSNHL) is a common otology emergency in the practice. Its severe hearing impairment and prognosis impair the quality of life. Given that cochlear hair cell vulnerability is not consistent across frequencies, this study aims to investigate the impact of frequency-specific hearing loss on prognosis in SSNHL. Methods: The study included 255 patients with full-frequency SSNHL. The baseline, clinical, and hearing characteristics, as well as possible cardiovascular predictors in blood, were collected for analysis. Results: The 4000 and 8000 Hz hearing levels in the responder group were significantly lower than those in the non-responder group (P=0.008, P<0.001), while the average hearing was not (P=0.081). Logistic regression showed that only vertigo (OR, 95% CI, 0.265, 0.102-0.684, p = 0.006) and 8000Hz hearing level (OR, 95% CI, 0.943, 0.916-0.971, p < 0.001) were strongly associated with treatment outcome. Conclusions: Compared with other frequencies, 8000Hz hearing level was closely related to prognosis in SSNHL. In an adjusted model, our study did not find an effect of mean hearing on prognosis in SSNHL. However, further multicenter prospective studies are needed for validation.